2010
DOI: 10.1002/jcp.22148
|View full text |Cite
|
Sign up to set email alerts
|

Cell death of prostate cancer cells by specific amino acid restriction depends on alterations of glucose metabolism

Abstract: Selective amino acid restriction targets mitochondria resulting in DU145 and PC3 prostate cancer cell death. This study shows that restriction of tyrosine and phenylalanine (Tyr/Phe), glutamine (Gln), or methionine (Met) differentially modulates glucose metabolism, glycogen synthase kinase 3beta (GSK3beta), p53, and pyruvate dehydrogenase (PDH) in these two cell lines. In DU145 cells, Gln and Met restriction increase glucose consumption, but Tyr/Phe restriction does not. Addition of glucose to culture media di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Activated TPKI/GSK-3β is shown to phosphorylate and suppress PDH, leading to disruption of glucose metabolism [46]. Similar results are obtained in DU145 and PC3 cells [47]. Cardiolipin is an important mitochondrial phospholipid, which is essential for the electron transport chain and ATP production.…”
Section: Gsk-3β Regulates Mitochondrial Bioenergeticssupporting
confidence: 68%
“…Activated TPKI/GSK-3β is shown to phosphorylate and suppress PDH, leading to disruption of glucose metabolism [46]. Similar results are obtained in DU145 and PC3 cells [47]. Cardiolipin is an important mitochondrial phospholipid, which is essential for the electron transport chain and ATP production.…”
Section: Gsk-3β Regulates Mitochondrial Bioenergeticssupporting
confidence: 68%
“…These studies showed that selective amino acid restriction promotes mitochondrial outer membrane permeabilization and reduces intracellular ATP in DU145 and PC3 prostate cancer cells (5). Results of the present study showed that specific amino acid restriction differentially modulates cellular metabolism in the two cell lines (15), including glucose metabolism, cellular redox status and antioxidant systems. The increased glycolytic activity (Warburg effect) of cancer cells enhances the proliferation and resistance of the cells to apoptosis (16).…”
Section: Discussionmentioning
confidence: 59%
“…The increased glycolytic activity (Warburg effect) of cancer cells enhances the proliferation and resistance of the cells to apoptosis (16). We previously found that the addition of glucose or pyruvate differentially reduces or postpones the apoptotic effect of specific amino acid restriction in DU145 and PC3 cells (15). …”
Section: Discussionmentioning
confidence: 99%
“…We found that 6 candidates were ranked in top 10 in both networks (Table 3). These top ranked metabolites were all reported to associate with initialization and development of prostate cancer [38][54]. For example, PROFANCY ranked the sorbitol at the first place.…”
Section: Resultsmentioning
confidence: 99%